REDUKSI THD MENGGUNAKAN POWER FACTOR CORRECTION (PFC) BOOST CONVERTER DENGAN MODE CCM - Sari, Widy Kartika; Djuriatno, Waru; Rusli, Moch. (Jurnal Mahasiswa TEUB, 2024)
This study discusses the application of Power Factor Correction (PFC) boost converter in Continuous Conduction Mode (CCM) to reduce Total Harmonic Distortion (THD) in a single-phase power system. Non-linear loads commonly used in electronic devices cause harmonic distortion that has a negative impact on power quality. By utilizing a PFC boost converter, this study aims to achieve THD reduction according to the IEEE 519-2014 standard. Testing was carried out using simulations on the Simulink Matlab R2021a software to compare a single-phase rectifier circuit and a single-phase rectifier circuit PFC boost converter with voltage and current control. The results of the simulation show that the application of the PFC boost converter successfully reduces THD significantly to below 5% at certain loads. From the results of all tests, PFC can reduce harmonic distortion,improve power efficiency and waveform quality, and show significant differences in the performance of single-phase rectifier circuits with and without PFC.Keywords: Single Phase Rectifier, Power Factor Correction (PFC), Boost Converter, Total Harmonic Distortion, Matlab R2021a